2017
DOI: 10.5851/kosfa.2017.37.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Meat Batter Added with Edible Silkworm Pupae (Bombyx mori) and Transglutaminase

Abstract: This study was conducted to investigate the physicochemical properties of meat batters prepared with fresh pork meat, back fat, water, and salt and formulated with three different amounts (5%, 10%, and 15%) of silkworm pupae (Bombyx mori) powder and transglutaminase (TG). Meat batters formulated with silkworm pupae powder showed significantly higher contents of protein and ash than control batter. Addition of silkworm pupae to batter also showed significantly lower cooking loss than the control. Moreover, meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 37 publications
9
45
2
3
Order By: Relevance
“…Kim et al [ 3 ] reported that pre-treated mealworm larvae and silkworm pupae, as a protein ingredient in emulsion sausage, and all emulsion sausages with pre-treated edible insect was higher than that of the control (without pre-treated edible insect). Park et al [ 33 ] reported that the hardness, gumminess, and chewiness of meat batter prepared with edible silkworm pupae increased with increase in edible silkworm pupae concentration. These results indicated an improvement in textural properties when edible silkworm was added to the meat batter.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [ 3 ] reported that pre-treated mealworm larvae and silkworm pupae, as a protein ingredient in emulsion sausage, and all emulsion sausages with pre-treated edible insect was higher than that of the control (without pre-treated edible insect). Park et al [ 33 ] reported that the hardness, gumminess, and chewiness of meat batter prepared with edible silkworm pupae increased with increase in edible silkworm pupae concentration. These results indicated an improvement in textural properties when edible silkworm was added to the meat batter.…”
Section: Resultsmentioning
confidence: 99%
“…Meat batters containing 5%, 10%, and 15% edible silkworm pupae and transglutaminase were added to frankfurters, resulting in higher protein and ash contents and significantly lower cooking loss weight than in the control. In addition, the silkworm pupae meat batter showed an increase in pH value, viscosity, and texture properties compared to the control (Park et al., ).…”
Section: Commercialization Of Edible Insectsmentioning
confidence: 99%
“…Kim et al [9] determined the effects of adding flour made from defatted mealworm larvae (Tenebrio molitor) and defatted silkworm pupae (Bombyx mori) and found that the added insect flours increased their cooking yield and hardness on emulsion sausages. Park et al [10] also found that adding transglutaminase to silkworm pupae flour resulted in improved physicochemical properties of meat batter.…”
Section: Introductionmentioning
confidence: 99%